CULTURE OF INNOVATIVE THINKING IN ORGANIZATIONS FACING THE COVID-19 PANDEMIC - ORTIZ ESAINE, Nicolás M. (2023)
The pandemic situation produces sociocultural changes and new businessparadigms. The culture of “Innovative Thinking” is key to the development ofsolution proposals in the face of a crisis scenario. This work seeks to demonstratethe relevance of this concept in organizations in the face of the pandemicFor the same, a review is made of the competence of “Innovative Thinking” insociety and business. It is used for its impact for the study, training and businessstrategic planning. This concept is broken down into the elements of Diagnosis,Research, Concept and Planning (DICP Method).It is validated through the gaze of key executives from the state, social, private,educational and union sectors; that allows us an overview of the context.